Phenotypical and functional profiles of natural killer cells exhibiting matrix metalloproteinase‐mediated CD16 cleavage after anti‐HIV antibody‐dependent activation. (7th June 2015) - Tang, C.‐C.; Isitman, G.; Bruneau, J.; Tremblay, C.; Bernard, N. F.; Kent, S. J.; Parsons, M. S.
Summary Natural killer (NK) cell‐mediated antibody‐dependent cellular cytotoxicity (ADCC) has been linked to protection from HIV infection and slower progression towards AIDS. However, antibody‐dependent activation of NK cells results in phenotypical alterations similar to those observed on NK cells from individuals with progressive HIV infection. Activation of NK cells induces matrix metalloproteinase (MMP)‐mediated cleavage of cell surface CD16. In the present study we assessed the phenotype and functional profile of NK cells exhibiting post‐activation MMP‐mediated CD16 cleavage. We found that NK cells achieving the highest levels of activation during stimulation exhibit the most profound decreases in CD16 expression. Further, we observed that educated KIR3DL1+ NK cells from human leucocyte antigen (HLA)‐Bw4‐carrying donors exhibit larger decreases in CD16 expression post‐activation than the KIR3DL1− NK cell subset containing cells educated via other inhibitory receptor/ligand combinations and non‐educated NK cells. Lastly, we assessed the ex‐vivo expression of CD16 on educated KIR3DL1+ NK cells and the KIR3DL1− NK cell subset from HLA‐Bw4‐carrying HIV‐uninfected and HIV‐infected donors. Suggestive of in‐vivo activation of KIR3DL1+ NK cells during HIV infection, CD16 expression was higher on KIR3DL1+ than KIR3DL1− NK cells in uninfected donors but similar on both subsets in HIV‐infected donors. These results are discussed in the context of how they may assist with understanding HIV disease progression and the design of immunotherapies that utilize antibody‐dependent NK cell responses.